Формування базової, професійної та самоосвітньої компетентності майбутніх інженерів-бакалаврів як важлива складова їх якісної підготовки у закладах вищої освіти - Романовський, Олександр Георгійович; Гура, Тетяна Віталіївна; Ігнатюк, Ольга Анатоліївна; Солодовник, Тетяна Олександрівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Особливу увагу приділено проблемам формування базової, професійної та самоосвітньої компетентності майбутніх інженерів-бакалаврів технічних закладів вищої освіти, яка залишається поза увагою науковців, незважаючи на те, що процес гуманізації вищої інженерної освіти вимагає від майбутніх фахівців постійного удосконалення професійних вмінь. Розглянуто детально ключові компоненти базової компетентності майбутніх інженерів. Запропоновано групи методів, що входять до процесу формування базової компетентності майбутніх інженерів-бакалаврів у ЗВО. Особливу увагу автори приділили якісній підготовці науково-педагогічних кадрів. Розкрито основні аспекти формування професійної компетентності бакалаврів, майбутніх хіміків-технологів, які сприяють підвищенню якості їх професійної підготовки. В статті акцентовано увагу на ролі внутрішньої мотивації здобувачів на процес успішного формування самоосвітньої компетентності. Доведено, що процес формування самоосвітньої компетентності майбутніх бакалаврів машинобудівних спеціальностей неможливий без діалогічної взаємодії "студент-викладач".

In the article special attention is paid to the problems of forming the basic, professional and self-educational competence of future bachelor engineers of technical higher education institutions, which remains outside the attention of scientists, despite the fact that the process of humanisation of higher engineering education requires from future specialists to constantly improve their professional skills. The key components of the basic competence of future engineers are considered in detail. The groups of methods that make up the process of forming the basic competence of future bachelor engineers in higher education institutions are proposed. The authors paid special attention to the quality of scientific and pedagogical staff training, which affects the process of forming professional competence. The main aspects of the formation of professional competence of bachelors, future chemical technologists, which contribute to improving the quality of their professional training, are considered. The main focus in the article is on the role of intrinsic motivation of students in the process of successful formation of self-educational competence. It is proved that the process of forming the self-educational competence of future bachelors of mechanical engineering specialties is impossible without the dialogue interaction between student and teacher.
Formation of basic, professional and self-educational competence of future bachelor engineers as an important component of their quality training in higher education institutions
Keywords: вища освіта; професійна підготовка; самоосвітня компетентність; майбутні інженери; науково-педагогічні кадри; заклади вищої освіти; внутрішня мотивація; self-educational competence; professional competence; future engineers; higher education institution